Prevalence and antimicrobial resistant Campylobacter spp. in broiler chicken carcasses and hygiene practises in informal urban markets in a low-income setting - Pius Okello; Olivia Graaf Bjöersdorff; Ingrid Hansson; Sofia Boqvist; Joseph Erume (PLoS ONE, 2025)
Campylobacteriosis is one of the most commonly reported foodborne diseases and is of particular importance in low-income countries. More data is needed to better understand the epidemiology of Campylobacter spp. in food sold at informal markets, where most people in low-income countries buy their food. This study aimed to determine the prevalence and antimicrobial resistance (AMR) of Campylobacter spp. among broiler chicken carcasses sold at informal urban markets in Uganda and to gain more knowledge about hygienic handling practices and awareness of foodborne bacterial diseases among the market vendors. In total, 120 broiler chicken carcasses from 30 different markets were analysed using ISO 10272 and confirmed by PCR. AMR analyses were performed using the disc diffusion test. Epidemiological data on food safety practices and awareness was collected from the vendors using a questionnaire. Campylobacter spp. was isolated from 66% (79/120) of the carcasses; 32% were C. jejuni, 14% were C. coli and 54% comprised of a mixture of both species. All C. jejuni isolates showed resistance to tetracycline, 88% to ciprofloxacin and 28% to erythromycin. Of the C. coli isolates, 82% showed resistance to tetracycline, 73% to erythromycin and the quinolones ciprofloxacin and nalidixic acid. More than half of the vendors had heard about food-borne illnesses, but none knew about Campylobacter spp., and the knowledge regarding hygienic practices was low. These data calls for urgent interventions to improve food safety, protect the public from foodborne illness, and prevent the spreading of AMR.